A high-elastic emulsion modified environmentally friendly inorganic composite spray material and its preparation method and application
By using high-elastic emulsion modified environmentally friendly inorganic composite spraying materials, combined with modified polymer and inorganic materials, the problems of slow construction speed, poor bonding strength, and poor waterproofing and impermeability of roadway surface protection materials are solved, and higher flexibility, impermeability and adhesion are achieved, extending the service life and reducing the construction workload.
Patent Information
- Application Number
- CN202411334435.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The existing roadway surface protective materials have problems such as slow construction speed, large material consumption, poor bonding strength, poor waterproofing and impermeability, and insufficient toughness, resulting in safety hazards and short service life.
High elastic emulsion is used to modify environmentally friendly inorganic composite spraying material, which consists of high elastic emulsion and inorganic composite powder material. By combining the modified polymer with the inorganic material, the flexibility, impermeability and adhesion of the material are improved.
It significantly improves the waterproofness, permeability, flexibility and adhesion of the roadway surface protective materials, reduces the dust generation and construction workload, extends the service life, and improves the sealing effect.
Smart Images

Figure BDA0005057879610000101 
Figure BDA0005057879610000121 
Figure BDA0005057879610000131
Abstract
Description
Technical Field
[0001] The invention belongs to the field of mine tunnel surface protection sealing and brightening spray composite materials, and specifically relates to a high-elastic emulsion modified environmentally friendly inorganic composite spray material and a preparation method and application thereof. Background Art
[0002] With the continuous expansion of mining scale, the amount of new tunnels excavated in mines remains high every year, especially in large-scale coal mining and ultra-long tunnel excavation, which makes the geological and environmental conditions faced by tunnel projects increasingly complex. The fractures, cracks, broken and loose rock layers, harmful gases, dripping water and other disasters in the mining tunnels cause safety hazards such as tunnel air leakage, tunnel coal oxidation and spontaneous combustion, and gravel falling, which puts higher requirements on the tunnel surface protection performance. The traditional tunnel surface protection material is shotcrete, which has sufficient density, high strength and good durability. However, since shotcrete is a brittle material with zero elongation, there are the following problems in the construction process: (1) The construction speed is slow, the material consumption is large, and the auxiliary transportation volume is large; (2) It is difficult for shotcrete to penetrate into the rock gaps and the bonding strength is poor; (3) There is a lot of dust during the construction process, which causes a large workload for workers and inhalation of a large amount of dust causes harm to the health of workers.
[0003] At the same time, in the underground tunnels, due to the increase in ground air temperature in summer, after the air enters the mine, the saturation capacity becomes smaller due to the gradual decrease in temperature. Part of the water in the mine air will condense into water droplets on the support or the wall of the shaft, so the walls of the shafts along the way appear damp. When the wall of the shaft is damp and contains a lot of water, the surrounding rock of the shaft absorbs the moisture in the air, causing the rock mass to absorb water and soften, causing the rock mass to soften and disintegrate. Therefore, the waterproof and anti-seepage performance of the tunnel support material is particularly important, which is a key issue in tunnel support. In addition, another key issue is that the micro-movement of the surrounding rock of the tunnel will cause the cracking of the support material. Once cracked, the purpose of sealing gas cannot be achieved, which will bring huge safety hazards. Therefore, the flexibility of the support material is also a must-pay attention to in the support of underground mine tunnels.
[0004] In recent years, thin spraying materials have gradually become popular. The spraying thickness of thin spraying materials is much smaller than that of traditional shotcrete, and the amount of slurry used is also significantly reduced, which solves the shortcomings of traditional shotcrete, such as slow construction speed, large material consumption, and large auxiliary transportation volume. At the same time, thin spraying materials can also penetrate into rock gaps, solving the problem of poor bonding strength in shotcrete. However, the existing thin spraying materials have poor waterproof and anti-seepage effects, especially when used for roadway lighting spraying, the service life is short, and it cannot be washed with water after being contaminated with dust. Secondly, the toughness of the spraying materials is insufficient, and it cannot solve the problem that the micro-movement of the surrounding rock of the roadway will cause the support materials to crack. Summary of the invention
[0005] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a highly elastic emulsion-modified environmentally friendly inorganic composite spray material and a preparation method and application thereof, which can be used for sealing coal faces in tunnels, spraying tunnel brightening materials, reinforcing coal bodies, preventing gas overflow, preventing weathering of coal and rock bodies, preventing water seepage in roofs, preventing rusting of metal materials, spraying windshield curtains into walls, and spraying closed walls to prevent air leakage.
[0006] To achieve the above object, the technical solution of the present invention is:
[0007] The first aspect of the present invention provides a highly elastic emulsion-modified environmentally friendly inorganic composite spray material, wherein the composite spray material is mixed with component A and component B:
[0008] The component A is a high elastic emulsion, which is composed of the following components by weight percentage:
[0009] 30%-40% silicone-acrylic emulsion, 20%-30% styrene-acrylate emulsion, 10%-20% VAE707 emulsion, 0.5%-1% fungicide, 0.5%-1% dispersant, 0.5%-1% film former, 0.5%-1% defoamer, and the rest is deionized water;
[0010] The B component is an inorganic composite powder material, which is composed of the following components by weight percentage:
[0011] 65%-80% ultrafine inorganic powder material, 10%-30% inorganic reinforcing material, 5%-10% colorant, 1%-5% composite steel bar rust inhibitor, 0.3%-3% composite flame retardant, 0.1%-0.5% rheology modifier, 0.01%-0.2% reinforcing anti-seepage agent, 0.01%-0.3% viscosity enhancer.
[0012] The second aspect of the present invention provides a method for preparing the high elastic emulsion modified environmentally friendly inorganic composite spraying material according to the first aspect, comprising the following steps:
[0013] After mixing silicone acrylic emulsion, styrene-acrylate emulsion and VAE707 emulsion according to weight proportion, defoamer, dispersant, film-forming agent and bactericide are added in sequence, and dispersed and stirred at a dispersion speed of 1000-1500 r / min and a dispersion time of 20-30 min to obtain component A;
[0014] The spodumene slag powder, blast furnace water-quenched slag, carbide slag and phosphogypsum are mixed in a weight ratio of 6:2:1:1, and calcined at 1200-1300°C for 2-4h. The calcined reactants are crushed and ground to a size of more than 2000 meshes to obtain an ultrafine inorganic powder material.
[0015] The inorganic reinforcing material, the toner, the steel bar rust inhibitor, the composite flame retardant, the rheology modifier, the reinforcing anti-seepage agent, the viscosity enhancer and the ultrafine inorganic powder material are uniformly mixed to obtain the B component.
[0016] When in use, component A and component B are mixed to obtain a high-elastic emulsion-modified environmentally friendly inorganic composite spray material.
[0017] Preferably, the weight ratio of component A to component B is 1:(1-2).
[0018] The third aspect of the present invention provides the use of the high-elastic emulsion modified environmentally friendly inorganic composite spray material described in the first aspect in surface protection sealing or brightening spraying of mine tunnels, coal mine tunnels, and tunnel tunnels.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The highly elastic emulsion-modified environment-friendly inorganic composite spray material provided by the present invention comprises a component A which uses a highly elastic composite emulsion to significantly improve the waterproofness, impermeability, flexibility, ductility, airtightness and adhesion of the material; and a component B which uses an inorganic composite powder material, which makes extensive use of industrial solid wastes such as spodumene slag, blast furnace water-quenched slag, carbide slag, phosphogypsum, etc., thereby greatly reducing the material production cost.
[0021] (2) The present invention improves the flexibility, impermeability and adhesion of the tunnel spraying material by combining inorganic materials with organic materials, that is, by modifying the inorganic materials with polymer emulsions, and greatly reduces the shrinkage of the material. At the same time, the color of the spraying material can be adjusted by the type and addition ratio of the toner to meet different color requirements.
[0022] (3) The present invention reduces dust generation and construction workload during construction, and provides a good construction environment for workers. The addition of preservatives, rust inhibitors, etc. can ensure a longer service life and protective sealing effect of the material. The material can be widely used in surface protection sealing, brightening spraying, etc. of mine tunnels, coal mine tunnels, and tunnel tunnels. DETAILED DESCRIPTION
[0023] In view of the fact that current coatings cannot effectively solve the problems of insufficient waterproofness, impermeability, flexibility, ductility, airtightness and adhesion on the surface of mine tunnels, the present invention provides a high-elastic emulsion-modified environmentally friendly inorganic composite spray material and its preparation method and application.
[0024] A typical embodiment of the present invention provides a highly elastic emulsion-modified environmentally friendly inorganic composite spray material, wherein the composite spray material is mixed with component A and component B:
[0025] The component A is a high elastic emulsion, which is composed of the following components by weight percentage:
[0026] 30%-40% silicone-acrylic emulsion, 20%-30% styrene-acrylate emulsion, 10%-20% VAE707 emulsion, 0.5%-1% fungicide, 0.5%-1% dispersant, 0.5%-1% film former, 0.5%-1% defoamer, and the rest is deionized water;
[0027] The B component is an inorganic composite powder material, which is composed of the following components by weight percentage:
[0028] 65%-80% ultrafine inorganic powder material, 10%-30% inorganic reinforcing material, 5%-10% colorant, 1%-5% composite steel bar rust inhibitor, 0.3%-3% composite flame retardant, 0.1%-0.5% rheology modifier, 0.01%-0.2% reinforcing anti-seepage agent, 0.01%-0.3% viscosity enhancer.
[0029] The components of the highly elastic emulsion-modified environmentally friendly inorganic composite spraying material of the present invention are described as follows:
[0030] The component A is a high elastic emulsion with outstanding characteristics such as good film-forming property, strong adhesion, high tensile strength, and strong weather resistance. The main components and their functions are analyzed as follows:
[0031] Silicone-acrylic emulsion: Acrylic resin is a polymer material with strong adhesion and film-forming properties, but acrylic resin has the disadvantages of poor water resistance, becoming brittle at low temperatures, and becoming sticky and losing strength at high temperatures. Polysiloxane chains have the characteristics of high flexibility, high and low temperature resistance, low surface energy, and good water resistance, but poor adhesion and film-forming properties. Silicone-acrylic emulsion can combine the strong adhesion and good film-forming properties of acrylic resin with the high elongation and good weather resistance of polysiloxane, and has excellent resilience, flexibility, adhesion, waterproofness, weather resistance, dust resistance, and UV resistance.
[0032] Styrene-acrylate emulsion: Styrene-acrylate emulsion is obtained by emulsion copolymerization of styrene and acrylate monomers. Styrene-acrylate emulsion has good adhesion, transparent film, and good water resistance, oil resistance, heat resistance and aging resistance.
[0033] VAE707 emulsion: A polymer emulsion composed of polyvinyl acetate (VAE), sodium dodecylbenzene sulfonate, polyacrylamide (PAM), sodium benzoate and other raw materials. It has excellent water resistance under static load conditions and can accommodate a large amount of cheap fillers while still maintaining excellent adhesion. It is very suitable for adhesive base materials that use fillers to control bonding strength and cost. The solid content of the VAE707 emulsion is more than 50%.
[0034] The synergistic combination of the above three emulsions has greatly improved the film-forming properties, ductility, bonding strength, tensile length, etc. of the material.
[0035] Bactericide: The bactericide preservative is a mixture of kasone and alkyl-substituted isoxathiazolinone.
[0036] The dispersant is one or more of a polycarboxylate ammonium salt dispersant, a polyacrylate ammonium salt dispersant, a polycarboxylate salt dispersant or a naphthalenesulfonate formaldehyde condensate dispersant.
[0037] Film-forming agent: Polyvinyl pyrrolidone, dodecyl alcohol ester and polyvinyl alcohol are mixed and used to promote the plastic flow and elastic deformation of latex particles, improve their cohesion, and thus form a film within a wide range of construction temperature.
[0038] Defoaming agent: one or more of the mineral oil defoaming agent, silicone defoaming agent, and polyether defoaming agent can be used to prevent air from being entrained during construction to form bubbles or bubbles from being generated due to reactions, which will affect the spraying effect and product quality.
[0039] The B component is an inorganic composite powder material with outstanding characteristics such as low fineness, good compatibility with emulsion, and low cost. Its composition and function are analyzed as follows:
[0040] Ultrafine inorganic powder materials: The main raw materials used are spodumene slag, phosphogypsum, and carbide slag, which are more economical.
[0041] Inorganic reinforcing material: It is composed of one or more of ordinary Portland cement, white cement, and fast-hardening sulphoaluminate cement. Its main function is to improve the strength of the material after solidification.
[0042] Colorant: one or more of titanium dioxide, ultrafine calcium carbonate powder, blue-green pigment, orange-yellow pigment, fluorescent brightener, and ultramarine, selected according to construction requirements.
[0043] Composite steel bar rust inhibitor: The composite steel bar rust inhibitor is composed of phosphate, polyhydroxy compounds or their metal salts, and sodium dodecyl sulfate. Its main function is to prevent rust after the material is sprayed onto metal anchor nets, metal pallets, metal anchor rods and other materials.
[0044] Composite flame retardant: composed of aluminum hydroxide and antimony trioxide, it mainly plays a role in improving the flame retardant and fireproof properties of the material.
[0045] Anti-seepage agent: composed of polysiloxane powder and calcium stearate, it improves the waterproof ability of the material.
[0046] Thickener: It is composed of two or more of hydroxypropyl methylcellulose, hydroxypropyl starch ether, instant powdered sodium silicate, instant carboxymethyl cellulose, and polyacrylamide. After adding, it can change the viscosity of the slurry, thereby improving the wall adhesion of the slurry and reducing the rebound of the material during spraying.
[0047] In some examples of this embodiment, the component A is composed of the following components by weight percentage:
[0048] 30%-40% silicone-acrylic emulsion, 20%-25% styrene-acrylate emulsion, 10%-15% VAE707 emulsion, 0.5%-1% bactericide, 0.5%-1% dispersant, 0.5%-1% film-forming agent, 0.5%-1% defoaming agent, and the rest is deionized water.
[0049] The B component is composed of the following components by weight percentage:
[0050] 65%-80% ultrafine inorganic powder material, 10%-21% inorganic reinforcing material, 5%-10% colorant, 2.4%-5% composite steel bar rust inhibitor, 0.5%-3% composite flame retardant, 0.1%-0.5% rheology modifier, 0.02%-0.2% reinforcing anti-seepage agent, 0.03%-0.3% viscosity enhancer.
[0051] In some examples of this implementation manner, the highly elastic emulsion-modified environmentally friendly inorganic composite spray material is formed by mixing component A and component B in a weight ratio of 1:(1-2).
[0052] In some examples of this implementation mode, in the component A, the solid content of the silicone acrylic emulsion is greater than 45%; the solid content of the styrene-acrylate emulsion is greater than 45%; and the solid content of the VAE707 emulsion is greater than 50%.
[0053] In some examples of this embodiment, in the component A, the bactericidal preservative is composed of kasone and alkyl-substituted isoxathiazolinone in a weight ratio of 1:4.
[0054] Preferably, the dispersant is a polycarboxylate ammonium salt dispersant;
[0055] Preferably, the film-forming agent is composed of polyvinyl pyrrolidone, dodecyl alcohol ester, and polyvinyl alcohol in a weight ratio of 1:1:3;
[0056] Preferably, the defoamer is one or more of a mineral oil defoamer, a silicone defoamer, and a polyether defoamer.
[0057] In some examples of this implementation mode, in the component B, the ultrafine inorganic powder material is prepared by mixing spodumene slag powder, blast furnace water-quenched slag, carbide slag and phosphogypsum in a weight ratio of 6:2:1:1, calcining at 1200-1300°C for 2-4h, drying and grinding to a size of 2000 mesh or above.
[0058] In some examples of this implementation mode, in the component B, the inorganic reinforcing material is one or more of ordinary Portland cement, white cement or fast-hardening sulphoaluminate cement.
[0059] Preferably, the toner is one or more of titanium dioxide, ultrafine calcium carbonate powder, blue-green pigment, orange-yellow pigment, fluorescent brightener or ultramarine;
[0060] Preferably, the composite steel bar rust inhibitor is composed of phosphate, polyhydroxy compound or its metal salt, and sodium dodecyl sulfate in a weight ratio of 5:5:1;
[0061] Preferably, the composite flame retardant is composed of aluminum hydroxide and antimony trioxide in a weight ratio of 1:(1-3);
[0062] Preferably, the rheology modifier includes one or more of a polycarboxylic acid superplasticizer, a naphthalene-based superplasticizer, an amino-based superplasticizer or an aliphatic superplasticizer;
[0063] Preferably, the anti-seepage agent is one or both of polysiloxane powder and calcium stearate;
[0064] Preferably, the viscosity enhancer is composed of two or more of hydroxypropyl methylcellulose, hydroxypropyl starch ether, instant powdered sodium silicate, instant carboxymethyl cellulose, and polyacrylamide.
[0065] A typical embodiment of the present invention provides a method for preparing the above-mentioned high-elastic emulsion modified environmentally friendly inorganic composite spraying material, which is characterized by comprising the following steps:
[0066] Add silicone acrylic emulsion, styrene-acrylate emulsion and VAE707 emulsion into the dispersion barrel in proportion, and then add defoamer, dispersant, film-forming agent and bactericide in sequence, and disperse and stir at a dispersion speed of 1000-1500r / min and a dispersion time of 20-30min to obtain component A.
[0067] The spodumene slag powder, blast furnace water-quenched slag, carbide slag and phosphogypsum are mixed in a weight ratio of 6:2:1:1, and calcined at 1200-1300°C for 2-4h. The calcined reactants are crushed and ground to 2000 mesh to obtain ultrafine inorganic powder material;
[0068] The inorganic reinforcing material, the toner, the steel bar rust inhibitor, the composite flame retardant, the rheology modifier, the reinforcing anti-seepage agent, the viscosity enhancer and the ultrafine inorganic powder material are uniformly mixed to obtain the B component.
[0069] When in use, component A and component B are mixed to obtain a high-elastic emulsion-modified environmentally friendly inorganic composite spray material.
[0070] Preferably, the weight ratio of component A to component B is 1:(1-2).
[0071] A typical embodiment of the present invention provides the use of the above-mentioned high-elastic emulsion modified environmentally friendly inorganic composite spray material in surface protection sealing or brightening spraying of mine tunnels, coal mine tunnels, and tunnel tunnels.
[0072] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments. The raw materials and reagents used in the following embodiments and comparative examples are conventional commercially available products and can be purchased.
[0073] Example 1
[0074] The component contents of a high elastic emulsion modified environmentally friendly inorganic composite spraying material are shown in Table 1.
[0075] Among them, the solid content of silicone acrylic emulsion is 45%; the solid content of styrene-acrylate emulsion is 45%; the solid content of VAE707 emulsion (commercial product, purchased from Beijing Oriental Petroleum Organic Chemical Plant) is 50%; the bactericide is composed of kason and alkyl-substituted isoxathiolanone in a weight ratio of 1:4; the dispersant is SN5027 polycarboxylate ammonium salt dispersant; the film-forming agent is composed of polyvinyl pyrrolidone, dodecyl alcohol ester, and polyvinyl alcohol in a weight ratio of 1:1:3; the defoamer is a mineral oil defoamer (commercial product, purchased from Guangdong Zhongke Hongtai New Materials Co., Ltd.).
[0076] The ultrafine inorganic powder material is prepared by mixing spodumene slag powder, blast furnace water-quenched slag, carbide slag and phosphogypsum in a weight ratio of 6:2:1:1, calcining at a high temperature of 1250°C for 2 hours, drying and grinding to 2000 mesh; the inorganic reinforcing material is fast-hardening sulphoaluminate cement; the colorant is composed of 3000 mesh ultrafine calcium carbonate powder, titanium dioxide, fluorescent brightener and ultramarine in a composition ratio of 2:2:0.5:0.1; the composite steel bar rust inhibitor is composed of phosphate, polyhydroxy compound or its metal salt and sodium dodecyl sulfate in a weight ratio of 5:5:1; the composite flame retardant is composed of aluminum hydroxide and antimony trioxide in a weight ratio of 1:3; the rheology modifier is a polycarboxylic acid high-efficiency water reducer; the reinforcing anti-seepage agent is polysiloxane powder and calcium stearate; the thickener is composed of hydroxypropyl methylcellulose and hydroxypropyl starch ether.
[0077] The preparation method adopted comprises the following steps:
[0078] Add silicone-acrylic emulsion, styrene-acrylate emulsion and VAE707 emulsion into a dispersion barrel in proportion, and then add defoamer, dispersant, film-forming agent and bactericide in sequence, and disperse and stir at a dispersion speed of 1000-1500 r / min and a dispersion time of 20-30 min to obtain component A;
[0079] Spodumene slag powder, blast furnace water-quenched slag, carbide slag, and phosphogypsum are calcined at 1250° C. for 2 h in a weight ratio of 6:2:1:1, and the calcined reactants are crushed and ground to 2000 mesh to obtain an ultrafine inorganic powder material;
[0080] The inorganic reinforcing material, the toner, the steel bar rust inhibitor, the composite flame retardant, the rheology modifier, the reinforcing anti-seepage agent, the viscosity enhancer and the ultrafine inorganic powder material are uniformly mixed to obtain the B component.
[0081] Before construction, component A and component B are mixed in a weight ratio of 1:1 to obtain an environmentally friendly composite spray material.
[0082] The obtained material performance indicators are shown in Table 3.
[0083] Example 2
[0084] The component contents of a high elastic emulsion modified environmentally friendly inorganic composite spraying material are shown in Table 1.
[0085] Among them, the solid content of silicone-acrylic emulsion is 45%; the solid content of styrene-acrylate emulsion is 45%; the solid content of VAE707 emulsion (commercial product purchased from Beijing Oriental Petroleum Organic Chemical Plant) is 50%; the bactericide is composed of kason and alkyl-substituted isoxazolinone in a weight ratio of 1:4; the dispersant is naphthalenesulfonic acid formaldehyde condensate sodium salt (commercial product, purchased from Hubei Ruike Chemical Co., Ltd.); the film-forming agent is composed of polyvinyl pyrrolidone, dodecyl alcohol ester, and polyvinyl alcohol in a weight ratio of 1:1:3; the defoamer is a silicone defoamer (THIX-278 silicone defoamer, a commercial product, purchased from Yantai Hengxin Chemical Technology Co., Ltd.).
[0086] The ultrafine inorganic powder material is obtained by calcining spodumene slag powder, blast furnace water-quenched slag, carbide slag and phosphogypsum at a weight ratio of 6:2:1:1 at a high temperature of 1250°C for 2 hours, drying and grinding to 2000 mesh; the inorganic reinforcing material is ordinary Portland cement; the colorant is composed of 3000 mesh ultrafine calcium carbonate powder, titanium dioxide, fluorescent whitening agent and ultramarine, and the composition ratio is 2:2:0.5:0.1; the composite steel bar rust inhibitor is composed of phosphate, polyhydroxy compound or its metal salt and sodium dodecyl sulfate at a weight ratio of 5:5:1; the composite flame retardant is composed of aluminum hydroxide and antimony trioxide at a weight ratio of 1:1; the rheology modifier is a polycarboxylic acid high-efficiency water reducer; the reinforcing anti-seepage agent is polysiloxane powder; and the viscosity enhancer is hydroxypropyl methylcellulose.
[0087] The preparation steps are consistent with those in Example 1.
[0088] The obtained material performance indicators are shown in Table 3.
[0089] Example 3
[0090] The components of a highly elastic emulsion-modified environmentally friendly inorganic composite spray material are shown in Table 1.
[0091] Among them, the solid content of silicone-acrylic emulsion is 45%; the solid content of styrene-acrylate emulsion is 45%; the solid content of VAE707 emulsion (commercial product, purchased from Beijing Oriental Petroleum Organic Chemical Plant) is 50%; the bactericide is composed of kason and alkyl-substituted isoxazolinone in a weight ratio of 1:4; the dispersant is SN5027 polycarboxylate ammonium salt dispersant; the film-forming agent is composed of polyvinyl pyrrolidone, dodecyl alcohol ester, and polyvinyl alcohol in a weight ratio of 1:1:3; the defoamer is a mixture of mineral oil defoamer and silicone defoamer in a weight ratio of 1:1 (commercial product, purchased from Guangdong Zhongke Hongtai New Materials Co., Ltd.).
[0092] The ultrafine inorganic powder material is obtained by calcining spodumene slag powder, blast furnace water-quenched slag, carbide slag and phosphogypsum at a weight ratio of 6:2:1:1 at a high temperature of 1250°C for 2 hours, drying and grinding to 2000 mesh; the inorganic reinforcing material is ordinary Portland cement; the colorant is composed of 3000 mesh ultrafine calcium carbonate powder, titanium dioxide, fluorescent whitening agent and ultramarine, and the composition ratio is 2:2:0.5:0.1; the composite steel bar rust inhibitor is composed of phosphate, polyhydroxy compound or its metal salt and sodium dodecyl sulfate at a weight ratio of 5:5:1; the composite flame retardant is composed of aluminum hydroxide and antimony trioxide at a weight ratio of 1:2; the rheology modifier is a polycarboxylic acid high-efficiency water reducer; the reinforcing anti-seepage agent is polysiloxane powder; and the viscosity enhancer is instant powdered sodium silicate.
[0093] The preparation steps are consistent with those in Example 1.
[0094] The obtained material performance indicators are shown in Table 3.
[0095] Example 4
[0096] The component contents of a high elastic emulsion modified environmentally friendly inorganic composite spraying material are shown in Table 1.
[0097] Among them, the solid content of silicone-acrylic emulsion is 45%; the solid content of styrene-acrylate emulsion is 45%; the solid content of VAE707 emulsion (commercial product, purchased from Beijing Oriental Petroleum Organic Chemical Plant) is 50%; the bactericide is composed of kason and alkyl-substituted isoxathiolanone in a weight ratio of 1:4; the dispersant is SN5027 polycarboxylate ammonium salt dispersant; the film-forming agent is composed of polyvinyl pyrrolidone, dodecyl alcohol ester, and polyvinyl alcohol in a weight ratio of 1:1:3; the defoamer is a polyether defoamer (commercial product, purchased from Zibo Jime Environmental Protection Technology Co., Ltd.).
[0098] The ultrafine inorganic powder material is composed of spodumene slag powder, blast furnace water-quenched slag, carbide slag, and phosphogypsum in a weight ratio of 6:2:1:1, calcined at a high temperature of 1250°C for 2 hours, and then dried and ground to 3000 mesh; the inorganic reinforcing material is ordinary Portland cement; the colorant is composed of 3000 mesh ultrafine calcium carbonate powder, titanium dioxide, fluorescent whitening agent, and ultramarine, and the composition ratio is 2:2:0.5:0.1; the composite steel bar rust inhibitor is composed of phosphate, polyhydroxy compound or its metal salt, and sodium dodecyl sulfate in a weight ratio of 5:5:1; the composite flame retardant is composed of aluminum hydroxide and antimony trioxide in a weight ratio of 1:1; the rheology modifier is a polycarboxylic acid high-efficiency water reducer; the reinforcing anti-seepage agent is calcium stearate; and the viscosity enhancer is polyacrylamide.
[0099] The preparation steps are consistent with those in Example 1.
[0100] The obtained material performance indicators are shown in Table 3.
[0101] Table 1 Component content of high elastic emulsion modified environmentally friendly inorganic composite spraying material
[0102]
[0103] Comparative Example 1
[0104] The component contents of a highly elastic emulsion-modified environmentally friendly inorganic composite spraying material are shown in Table 2.
[0105] The difference from the components in Example 1 is that no styrene-acrylate emulsion is added, and the proportions of other components are the same as those in Example 1. The preparation steps are the same as those in Example 1.
[0106] The obtained material performance indicators are shown in Table 3.
[0107] Comparative Example 2
[0108] The component contents of a highly elastic emulsion-modified environmentally friendly inorganic composite spraying material are shown in Table 2.
[0109] The components are different from those in Example 1 in that VAE707 emulsion is not added, the proportions of silicone-acrylic emulsion and styrene-acrylate emulsion are increased synchronously according to those in Example 1, and the other components are the same as those in Example 1. The preparation steps are the same as those in Example 1.
[0110] The obtained material performance indicators are shown in Table 3.
[0111] Comparative Example 3
[0112] The component contents of a highly elastic emulsion-modified environmentally friendly inorganic composite spraying material are shown in Table 2.
[0113] The components are different from those in Example 1 in that no silicone-acrylic emulsion is added, the proportions of VAE707 emulsion and styrene-acrylate emulsion are increased synchronously according to those in Example 1, and the other components are the same as those in Example 1. The preparation steps are the same as those in Example 1.
[0114] The obtained material performance indicators are shown in Table 3.
[0115] Comparative Example 4
[0116] The component contents of a highly elastic emulsion-modified environmentally friendly inorganic composite spraying material are shown in Table 2.
[0117] The components of the present invention are different from those of Example 1 in that the ultrafine inorganic powder material is not added, and the ultrafine powder material is replaced by an inorganic reinforcing material, and the other components are the same as those of Example 1. The preparation steps are the same as those of Example 1.
[0118] The obtained material performance indicators are shown in Table 3.
[0119] Comparative Example 5
[0120] The component contents of a highly elastic emulsion-modified environmentally friendly inorganic composite spraying material are shown in Table 2.
[0121] The components are different from those in Example 1 in that no inorganic reinforcing material is added, and the inorganic reinforcing material is replaced by an ultrafine powder material, and the other components are the same as those in Example 1. The preparation steps are the same as those in Example 1.
[0122] The obtained material performance indicators are shown in Table 3.
[0123] Comparative Example 6
[0124] The component contents of a highly elastic emulsion-modified environmentally friendly inorganic composite spraying material are shown in Table 2.
[0125] The difference from the components of Example 1 is that no tackifier is added, and the other components are the same as those of Example 1. The preparation steps are the same as those of Example 1.
[0126] The obtained material performance indicators are shown in Table 3.
[0127] Comparative Example 7
[0128] The component contents of a highly elastic emulsion-modified environmentally friendly inorganic composite spraying material are shown in Table 2.
[0129] The components of the present invention are different from those of Example 1 in that pure n-butyl acrylate is used instead of silicone acrylic emulsion, and the other components are the same as those of Example 1. The preparation steps are the same as those of Example 1.
[0130] The obtained material performance indicators are shown in Table 3.
[0131] Comparative Example 8
[0132] The component contents of a highly elastic emulsion-modified environmentally friendly inorganic composite spraying material are shown in Table 2.
[0133] The components of Example 1 are different in that a new environmentally friendly cementitious material is used, which is obtained by calcining blast furnace water-quenched slag, coal gangue, desulfurized gypsum powder, red mud, fly ash, and limestone in a weight ratio of 8:2:3:2:2:3 at high temperature, drying, and grinding, to replace the ultrafine inorganic powder material, and the other components are the same as those of Example 1. The preparation steps are the same as those of Example 1.
[0134] The obtained material performance indicators are shown in Table 3.
[0135] Comparative Example 9
[0136] The component contents of a highly elastic emulsion-modified environmentally friendly inorganic composite spraying material are shown in Table 2.
[0137] The difference from the components of Example 1 is that a composite cross-linking film-forming agent is used, which is composed of modified bentonite, borax, and silicate in a weight ratio of 0.9-1.1:0.5:2. The film-forming agent (composed of polyvinyl pyrrolidone, dodecyl alcohol ester, and polyvinyl alcohol in a weight ratio of 1:1:3) is replaced, and the other components are the same as those of Example 1. The preparation steps are the same as those of Example 1.
[0138] The obtained material performance indicators are shown in Table 3.
[0139] Table 2 Component content of composite spraying material
[0140]
[0141] Table 3 Performance parameters of high elastic emulsion modified environmentally friendly inorganic composite spraying materials
[0142]
[0143]
[0144]
[0145] From the results in Table 3, it can be seen that the comprehensive performance of the high-elastic emulsion modified environmentally friendly inorganic composite spray material obtained in Examples 1-4 is better than that of Comparative Examples 1-9. Comparison of Comparative Examples 1-3 and 7 with Example 1 shows that the mixed emulsion is more conducive to enhancing the mechanical properties of the high-elastic emulsion modified environmentally friendly inorganic composite spray material than the single emulsion. This shows that the three emulsions work together to greatly improve the film-forming property, ductility, bonding strength, tensile length, etc. of the material. Compared with Example 1, Comparative Examples 4-5 have poor wall hanging properties and slight flow; at the same time, the surface drying time, rebound rate and crack sealing are poor, which shows that ultrafine inorganic powder materials and inorganic reinforcing materials directly affect the construction progress, product stability and sealing performance.
[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A highly elastic emulsion modified environmentally friendly inorganic composite spraying material, characterized in that: The composite spray material is mixed with component A and component B: The component A is a high elastic emulsion, which is composed of the following components by weight percentage: 30%-40% silicone-acrylic emulsion, 20%-30% styrene-acrylate emulsion, 10%-20% VAE707 emulsion, 0.5%-1% fungicide, 0.5%-1% dispersant, 0.5%-1% film former, 0.5%-1% defoamer, and the rest is deionized water; The component B is an inorganic composite powder material, which is composed of the following components by weight percentage: 65%-80% ultrafine inorganic powder material, 10%-30% inorganic reinforcing material, 5%-10% toner, 1%-5% composite steel bar rust inhibitor, 0.3%-3% composite flame retardant, 0.1%-0.5% rheology modifier, 0.01%-0.2% reinforcing anti-seepage agent, 0.01%-0.3% viscosity enhancer; The sum of all components in the B component is 100%; The ultrafine inorganic powder material is prepared by mixing spodumene slag powder, blast furnace water-quenched slag, carbide slag and phosphogypsum in a weight ratio of 6:2:1:1, calcining at 1200-1300° C. for 2-4 hours, drying and grinding to a size of 2000 mesh or more. The inorganic reinforcing material is one or more of ordinary Portland cement, white cement or fast-hardening sulphoaluminate cement.
2. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: The component A is composed of the following components by weight percentage: 30%-40% silicone-acrylic emulsion, 20%-25% styrene-acrylate emulsion, 10%-15% VAE707 emulsion, 0.5%-1% fungicide, 0.5%-1% dispersant, 0.5%-1% film former, 0.5%-1% defoamer, and the rest is deionized water; The component B is composed of the following components by weight percentage: 65%-80% ultrafine inorganic powder material, 10%-21% inorganic reinforcing material, 5%-10% colorant, 2.4%-5% composite steel bar rust inhibitor, 0.5%-3% composite flame retardant, 0.1%-0.5% rheology modifier, 0.02%-0.2% reinforcing anti-seepage agent, 0.03%-0.3% viscosity enhancer.
3. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: The composite spray material is formed by mixing component A and component B in a weight ratio of 1:(1-2).
4. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the component A, the solid content of the silicone-acrylic emulsion is more than 45%; the solid content of the styrene-acrylate emulsion is more than 45%; and the solid content of the VAE707 emulsion is more than 50%.
5. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the component A, the fungicide is composed of kasone and alkyl-substituted isoxathiazolinone in a weight ratio of 1:
4.
6. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the component A, the dispersant is one or more of a polyacrylate ammonium salt dispersant, a polycarboxylate dispersant or a naphthalenesulfonate formaldehyde condensate dispersant.
7. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the component A, the film-forming agent is composed of polyvinyl pyrrolidone, dodecyl alcohol ester and polyvinyl alcohol in a weight ratio of 1:1:
3.
8. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the component A, the defoamer is one or more of a mineral oil defoamer, a silicone defoamer, and a polyether defoamer.
9. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the B component, the ultrafine inorganic powder material is obtained by mixing spodumene slag powder, blast furnace water-quenched slag, carbide slag and phosphogypsum in a weight ratio of 6:2:1:1, calcining at a high temperature of 1250° C. for 2 hours, drying and grinding to a size of more than 2000 mesh.
10. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the component B, the toner is one or more of titanium dioxide, ultrafine calcium carbonate powder, blue-green pigment, orange-yellow pigment, fluorescent whitening agent or ultramarine.
11. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the component B, the composite steel bar rust inhibitor is composed of phosphate, polyhydroxy compound or its metal salt, and sodium dodecyl sulfate in a weight ratio of 5:5:
1.
12. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the B component, the composite flame retardant is composed of aluminum hydroxide and antimony trioxide in a weight ratio of 1: (1-3).
13. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the component B, the rheology modifier includes one or more of a polycarboxylic acid high-efficiency water reducer, a naphthalene-based high-efficiency water reducer, an amino high-efficiency water reducer or an aliphatic water reducer.
14. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the component B, the anti-seepage agent is one or both of polysiloxane powder and calcium stearate.
15. The highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to claim 1, characterized in that: In the component B, the viscosity enhancer is two or more of hydroxypropyl methylcellulose, hydroxypropyl starch ether, instant powdered sodium silicate, instant carboxymethyl cellulose or polyacrylamide.
16. A method for preparing the highly elastic emulsion modified environmentally friendly inorganic composite spraying material according to any one of claims 1 to 15, characterized in that: The following steps are involved: The silicone-acrylic emulsion, styrene-acrylate emulsion and VAE707 emulsion are mixed in proportion, and then a defoamer, a dispersant, a film-forming agent and a bactericide are added in sequence, and dispersed and stirred at a dispersion speed of 1000-1500 r / min and a dispersion time of 20-30 min to obtain component A; The inorganic reinforcing material, the toner, the steel bar rust inhibitor, the composite flame retardant, the rheology modifier, the reinforcing anti-seepage agent, the tackifier and the ultrafine inorganic powder material are uniformly mixed to obtain component B; When in use, component A and component B are mixed to obtain a high-elastic emulsion-modified environmentally friendly inorganic composite spray material.
17. Use of the highly elastic emulsion modified environmentally friendly inorganic composite spray material according to any one of claims 1 to 15 in surface protection sealing or brightening spraying of mine tunnels, coal mine tunnels, and tunnel tunnels.
Citation Information
Patent Citations
Flexible spraying material for mine laneway supporting and preparation method and application of flexible spraying material
CN111533518A
Flexible spraying material for tunnel roadway support and preparation method and application thereof
CN111533519A